The Role of Social Media in Spreading the Culture of Love and Hate in the Society of Thi Qar Governorate: A Descriptive Analytical Study - Mohammed, Salm Sami; bachay, nabeel thajeel (Thi Qar Arts Journal, 2024)
The study aimed to understand the role of social media in spreading the culture of love and hate in the society of Dhi Qar Governorate through its various types, specificities, and multiple functions. This was achieved through a questionnaire for the targeted sample in the study. The study used the descriptive analytical method with a survey technique for a sample of 100 people from different segments of the society of Dhi Qar Governorate who use various social media platforms.The study reached a set of conclusions, the most important of which are:• The most important factors that help spread the culture of love through social media in the society of Dhi Qar Governorate are the continuous interaction by users. The most important factors that help spread the culture of hate through social media are the social, economic, and political conditions of the governorate.• The most prominent content that drives the sample to interact with content promoting the culture of love is video clips, while the most prominent content that drives the sample to interact with content promoting the culture of hate is published texts.• The main reasons and motives that social media seeks to spread the culture of hate in the society of Dhi Qar Governorate are to satisfy the desires of the audience.